Coastal habitat conservation using community education as a tool: a case study in Mukim Tanjung Kupang, Johor / Serina Abdul Rahman - Abdul Rahman, Serina (2014)
Mukim Tg Kupang and its adjacent coastal habitats harbour a rich variety of seagrass meadows, mangroves and rocky shores which are home to myriad endangered species and other cryptic fauna. However this area is slated for development and the local fishing community who depend on it needs to be equipped with the ability to cope with inevitable urbanisation and change. This case study proposed a long-term science-based environmental education program aimed at a primary audience of local children and youth (aged 6-18, n=34) that would disseminate conservation knowledge and encourage environmentally-friendly behaviour and a conservation mindset to the wider community. After two years of the education program, another year on-site focussed on developing community empowerment through an extended initiative that roped in older youth (aged 19-28) and local women, and this proved to be the key success factor in the study. Document analysis and the collation of local ecological knowledge by local youth as well as their habitat monitoring data resulted in an assessment of local natural resources and provide an indication of the habitats’ potential economic value. A paired t-test of the primary audience’s (n=31) pre- and post-test results indicated significant knowledge gain while the one-way ANOVA and the Newman-Keuls post hoc test demonstrated significant learning across content categories, with the history/socioeconomics topics being significantly different from the rest. Extensive qualitative analysis through post-program interviews, structured observation checklists, detailed field notes and other sources, supplemented by triangulation of data for additional reliability and validity showed both intra- and intergenerational information dissemination to a secondary audience of local and visiting peers and elders. The emergent community education and empowerment framework and the Kelab Alami methodology are proposed as a model for coastal habitat conservation. Put through a preliminary test in Fraser’s Hill Pahang, recommendations for the application of these tools in other habitats and locations are also suggested. The primary participants in this study (the youth) have shown that they have become effective agents of change and drivers of conservation action and attitudes in Mukim Tg Kupang, as well as capable local habitat experts. The program has enabled the youth and the wider community to better cope with impending change and take the first steps towards ensuring their participation and inclusion in inclusive sustainable development.